Analisis Timbulan Sampah dan Pemanfaatan Sampah Organik Berbasis Eco enzyme Pada Kawasan Wisata Kuliner Air Salobar, Kota Ambon - Tuhumury, Novianty C.; Sangadji, Dharsa M. D.; Ummah, Arisha N. A. (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
The existence of waste in tourist areas does not only have a negative impact locally but also globally. The process of decomposing organic waste produces greenhouse gases, while plastic inorganic waste which is difficult to decompose causes higher levels of microplastic pollution in the environment. The purpose of this study is to analyze waste generation and to utilize organic waste produced in the Air Salobar Culinary Tourism area to become eco enzyme. This research was conducted in March-June 2023 in the Air Salobar Culinary Tourism area, Nusaniwe District, Ambon City. Retrieval and analysis of inorganic waste data refers to SNI 19-3964-1994. The classification of inorganic waste is based on the classification of marine debris according to UNEP (United Nations Environment Programme). Collection of organic waste and processing it into eco enzyme using the observation method. The resulting data is then displayed in the form of tables, diagrams and figures for further discussion. The results of the study proved that the total weight of waste generated in this tourist area was 215.91 kg consisting of 213.37 kg of organic waste and 2.54 kg of inorganic waste. The weight of waste generation both organic and inorganic waste generated during 10 days of observation was 0.22 kg/person/day with a volume of waste generation of 0.84 liter/person/day. The potential for recycling inorganic waste is 99% of the total weight of inorganic waste produced. The potential for recycling organic waste into eco enzyme is 73.16 kg or 80% of the weight of the fruit peel organic waste produced. The eco enzyme solution obtained after 3 months of fermentation is 6.2 liter. The results of this study indicate that the waste generated in the Air Salobar Culinary Tourism area can be recycled which is beneficial both ecologically and economically.